Hybrid Storage Integration: Bridging On-Premises and Cloud through APIs - Venkatachala Nivas Chainuru (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution, implementation, and benefits of API-driven hybrid storage architectures in modern enterprise environments. The article examines how organizations increasingly adopt hybrid approaches that blend on-premises infrastructure with cloud capabilities to address complex storage challenges. It investigates market trends driving this transition, including cloud-first strategies, performance requirements, and regulatory considerations. The article details key components of successful API-driven hybrid storage implementations, including unified API frameworks, data orchestration services, storage virtualization, metadata management, and comprehensive security controls. Implementation benefits are quantified across multiple dimensions, including operational consistency, flexible resource allocation, cost optimization, migration efficiency, enhanced data protection, and performance optimization. The article concludes with critical technical implementation considerations necessary for successful deployments, providing organizations with a roadmap for implementing effective hybrid storage strategies.